Pengaruh Kualitas Produk, Harga dan Citra Merek terhadap Keputusan Pembelian Iphone di Sidoarjo - Rabbani, Reyhan Nur; Mulyati, Awin; Nasution, Ute Chairuz (Research Journal of Social Science and Economics, 2025)
In the development of today’s digital world where communication is a very important requirement for every level of society. Cellphones are a technology that is experiencing rapid development, so many companies are competing to increase the superiority of their products. New brands are popping up in the mobile phone industry with the aim of creating excellent products. The need for communication tools, through the purpose of this study was to examine the effect of product quality, brand image, and price, both individually and simultaneously, on the purchase decision of an iPhone smartphone in Sidoarjo. These three variables are one of the things that consumers pay close attention to in choosing smartphone products and there are previous studies which show the significance level of the three research variables on purchasing decisions that are inconsistent. The sampling method used was through a non-probability quantitative technique with purposive sampling. From the partial and simultaneous hypothesis testing it is proven that the variables of Product Quality, Price and Brand Image have a significant effect on Iphone Smartphone Purchase Decisions in Sidoarjo. This means that if product quality, price and brand image are improved, purchasing decisions will also increase. This study applies several data tests, namely data instrument tests, classical assumption tests and multiple linear regression. This study can be drawn a conclusion that there is an overall significant effect on the variables of product quality, price and brand image on purchasing decisions on Iphone smartphone users. The results of the t test state that the variable product quality, price and brand image have a positive and significant influence on a purchase decision.